The Influence of Lecturer Interpersonal Communication on the Academic Achievement of Students of the 2019 Stambuk Communication Science Study Program, Faculty of Social Sciences, UIN North Sumatra, Medan - Ramadhan, Rahmad; Ritonga, Muhammad Husni (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Interpersonal communication is a process of communication or interaction that exchanges ideas, either language or symbols that can be understood by others through spoken, written and non-verbal channels. This interpersonal communication has the goal of obtaining a good relationship between lecturers and students in terms of academic achievement, obtaining learning information and influencing behavior patterns and attitudes of communication between lecturers and students. The academic community, including lecturers, education staff and students, must improve interpersonal communication in supporting learning activities, research and community service. The measure of the success of a student is influenced by the lecturer as a teacher who continues to provide direction, communicate and exchange information. This study aims to see how influential interpersonal communication carried out by lecturers is on student academic achievement in the 2019 Stambuk Communication Studies Program, Faculty of Social Sciences, UIN North Sumatra Medan. With a sample of 39 students from a total population of 155 people. The method used in this study is to use quantitative methods and use simple regression tests to manage data. Based on the results of research on the Effect of Lecturer Interpersonal Communication on Student Academic Achievement in the Stambuk 2019 Communication Studies Program, Faculty of Social Sciences, Uin Sumatera Utara, Medan, found results. The Effect of Lecturer Interpersonal Communication Variables on Student Academic Achievement of the 2019 Stambuk Communication Study Program, Faculty of Social Sciences, UIN North Sumatra. Based on the results of the test for the coefficient of determination in the simple regression test using the SPSS program, an RSquare value of 0.489 was obtained, which means that the independent variable is able to explain the dependent variable by 49% and the remaining 55% is explained by other variables that cannot be explained in this study.